2017
DOI: 10.1186/s12860-017-0150-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targets and signaling pathways regulated by nuclear translocation of syndecan-1

Abstract: BackgroundThe cell-surface heparan sulfate proteoglycan syndecan-1 is important for tumor cell proliferation, migration, and cell cycle regulation in a broad spectrum of malignancies. Syndecan-1, however, also translocates to the cell nucleus, where it might regulate various molecular functions.ResultsWe used a fibrosarcoma model to dissect the functions of syndecan-1 related to the nucleus and separate them from functions related to the cell-surface. Nuclear translocation of syndecan-1 hampered the proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 98 publications
(101 reference statements)
1
20
0
Order By: Relevance
“…Our results further support that EGR1 directly regulates HPSE transcription. Data in fibrosarcoma cells suggest that the nuclear localization of Sdc-1 is a critical factor in regulating EGR1 expression, as expression of Sdc-1 lacking its nuclear localization signal resulted in upregulation of EGR1 (49). Therefore, the upregulation of EGR1 observed in Sdc-1depleted Caco2 cells in our study may have been due to the reduction in nuclear, Sdc-1.…”
Section: Discussionmentioning
confidence: 51%
“…Our results further support that EGR1 directly regulates HPSE transcription. Data in fibrosarcoma cells suggest that the nuclear localization of Sdc-1 is a critical factor in regulating EGR1 expression, as expression of Sdc-1 lacking its nuclear localization signal resulted in upregulation of EGR1 (49). Therefore, the upregulation of EGR1 observed in Sdc-1depleted Caco2 cells in our study may have been due to the reduction in nuclear, Sdc-1.…”
Section: Discussionmentioning
confidence: 51%
“…As previously reported, syndecan-1 (SDC1) is a cell adhesion molecule expressed on the cell surface, which is usually characterized by covalent bonds of heparan sulfate (HS) (4). Ibrahim et al (5) reported the involvement of SDC1 in breast cancer, suggesting that this protein maintains cell phenotype and inhibits cell migration, whereas when SDC1 is isolated from the cell surface, cells may exhibit enhanced proliferative and migratory abilities.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the normal murine mammary gland and in human lung carcinoma epithelial cells, SDC1 cell surface expression is upregulated by TGF-β in a post-translational and Protein Kinase A (PKA) dependent manner[146]. Microarray studies from fibrosarcoma cells revealed that nuclear SDC1, promotes TGF-β signaling activity[147]. In mesothelioma cells, however, TGF-β inhibited nuclear translocation of SDC1 to reduce cell proliferation[148].…”
Section: Cell Signaling Regulation By Dually Modified Transmembranmentioning
confidence: 99%